A conjecture about the non-trivial zeroes of the Riemann zeta function - Alcántara Bode, Julio (Pro Mathematica, 2007)
Some heuristic arguments are given in support of the following conjecture: If the Riemann Hypothesis (RH) does not hold then the number of zeroes of the Riemann zeta function with real part ? > ½ is infinite.